(untitled) (Eurasian Journal of Philology Science and Education, 2025)
In contemporary linguistics, there is a growing body of theoretical research that interprets linguistic phenomena not only from structural or functional perspectives but also as components of a complex, open, and continuously evolving system. Within this scholarly context, the integration of the interdisciplinary methodological potential of synergetics into linguistic research has become increasingly relevant. However, the synergetic metalanguage, originally developed within the natural sciences, gives rise to a number of theoretical and terminological challenges when applied to the description of linguistic processes. This article addresses these issues by examining the methodological relationship between the synergetic metalanguage and dynamic processes operating within language. The study aims to substantiate the applicability of the conceptual and categorical apparatus of synergetics to linguistic research. The core categories of synergetics are treated as heuristic tools that make it possible to interpret the internal dynamics of the language system, mechanisms of instability, and processes of change. Language is conceptualized as a natural, open, and nonlinear system, while language evolution is analyzed through the explanatory potential of such concepts as self-organization (шоғырландыру), bifurcation, fluctuation, chaos, and attractor. Particular attention is paid to the terminological justification of the Kazakh equivalent shogyrlandyru for the concept of self-organization, grounded in principles of national scientific cognition and terminology formation. The article contributes to the systematization of the theoretical foundations of linguosynergetics in Kazakh linguistics, advances the analysis of language change through dynamic models, and promotes the consolidation of interdisciplinary methodology in contemporary linguistic scholarship. Keywords: synergetics, linguosynergetics, metalanguage, dynamic system, self-organization, language evolution.